Successful Treatment of Spontaneous Cerebrospinal Fluid Rhinorrhea With Endoscopic Third Ventriculostomy and Lumboperitoneal Shunt: A Case Report - Tang, Chao; Zhu, Junhao; Feng, Kaiyang; Yang, Jin; Cong, Zixiang; Cai, Xiangming; Qiao, Liang; Ma, Chiyuan (Frontiers in Neuroscience, 2020)
Spontaneous cerebrospinal fluid (CSF) rhinorrhea are associated with elevated intracranial pressure (ICP), which are rarely stopped without surgical intervention. Endoscopic endonasal repair is typically warranted for CSF rhinorrhea. However, the recurrence rate of CSF leaks after the endoscopic endonasal repair of skull base defects due to ICP is usually high. We describe a 25-year-old man without history of head injury, tumor or obesity. The onset of his symptoms was about 1 week with a persistent clear left nostril rhinorrhea. CT and MRI showed signs of CSF in the left sphenoidal sinus, meningocele in the left frontal sinus, empty sella, hydrocephalus and Chiari I malformation (CIM). Cine-MRI revealed the flow of CSF was obstructed at aqueduct and the outlet of the fourth ventricle. Endoscopic third ventriculostomy (ETV) was performed for the patient with obstructive hydrocephalus. Post-operative CSF pressure measurement demonstrated elevated ICP. The patient still has a symptom of CSF rhinorrhea and subsequently underwent lumboperitoneal shunt (LPS) for treatment of intracranial hypertension. The patient showed a prompt resolution of CSF leak. Ten months later, the patient show a significant improvement in herniated tonsil and cessation of CSF rhinorrhea.